Analysis of Internal Control of Receivables at PT Sucifindo Jakarta Branch - Pradani Janatul Umah; Agus Prasetyo; Camelia Putrini (MultiTech Publisher, 2024)
In the midst of intense business competition, companies are required to be able to dominate the market, so companies need to implement a credit sales strategy so that the number of sales increases. In general, receivables arise due to transactions selling goods or services on credit. Too large an investment in receivables can result in slow turnover of working capital, resulting in a smaller company's ability to increase sales volume. As a result, the company has less opportunity to generate profits or profit. The aim that is expected to be achieved from this research is to analyze bad debts made by PT. SUCOFINDO Jakarta Branch. The analytical method used in this research is descriptive analysis to discuss problems that describe, describe, compare data or situations, describe and explain research results so that conclusions can be drawn. PT. SUCOFINDO Jakarta Branch has carried out receivables management and accounts receivable analysis well. Receivables that are overdue ≤ 90 days and receivables that are 91-360 days old can be properly collected. Meanwhile, receivables that are > 1 year old are categorized as bad debts which will be set aside as bad debts of 65.7%.